Peptidomic changes of saliva after non‐surgical treatment of stage I/II generalized periodontitis. (19th March 2021) - Yuan, Chao; Ma, Zhangke; Tong, Peiyuan; Yu, Shunlan; Li, Yi; Gallagher, Jennifer Elizabeth; Sun, Xiangyu; Zheng, Shuguo
Abstract: Objective: To explore the changes of peptidome profiles of saliva, serum, and gingival crevicular fluid (GCF) before and after non‐surgical periodontal treatment in patients with generalized periodontitis (stage I/II). Subjects and methods: Saliva, serum, and GCF samples were collected from 17 patients at baseline (T0 ), one week after ultrasonic supragingival scaling (T1 ) and eight weeks after subgingival scaling and root planning (T2 ). Matrix‐assisted laser desorption/ionization time‐of‐flight mass spectrometry (MALDI‐TOF MS) was carried out to detect changes in peptidomic profiles. Then, nano‐liquid chromatography‐electrospray ionization‐tandem mass spectrometry (nano‐LC/ESI‐MS/MS) was performed to identify potential peptide biomarkers. Results: Most of the peptides from the patients exhibited a decreasing trend from the time point of pretreatment to that of post‐treatment. Cluster analysis and scatter plots using these peptides indicated that salivary peptidome has an acceptable capability of reflecting the status of stage I/II generalized periodontitis. Seven of these peptides were successfully identified as α‐1‐antitrypsin, immunoglobulin κ variable 4‐1, haptoglobin, and immunoglobulin heavy constant γ2. Conclusions: Certain peptides in saliva, serum, and GCF were down‐regulated after non‐surgical periodontal treatment, demonstrating the application prospects of saliva in monitoring and surveillance of periodontal diseases in both clinical settings and communities.